Regioselective intramolecular cyclization of o-alkynyl arylamines with the in situ formation of ArXCl to construct poly-functionalized 3-selenylindoles. Issue 9 (21st February 2023) - Yu, Minhui; Jin, Tao; Wang, Xiaohua; Li, Haohu; Ji, Decai; Yao, Jinzhong; Zeng, Heyang; Shi, Senlei; Xu, Kaimeng; Zhang, Lianpeng
Abstract : In this paper, we have developed a metal-free protocol for the controllable synthesis of various 3-selenyl/sulfenyl/telluriumindoles from the regioselective intramolecular cyclization reactions of in situ generated RXCl with o -alkynyl arylamines. Abstract : In this article, a practical and metal-free method for the synthesis of poly-functionalized 3-selenyl/sulfenyl/telluriumindoles from o -alkynyl arylamines has been achieved. In this protocol, the in situ formation of selenenyl chloride, sulfenyl chloride or tellurenyl chloride is considered as the key intermediate and the 3-selenyl/sulfenyl/telluriumindoles can be obtained in good to excellent yields. Furthermore, the product 2-phenyl-3-(phenylselanyl)-1-tosyl-1 H -indole can be selectively oxidized to compounds 2-phenyl-3-(phenylseleninyl)-1-tosyl-1 H -indole and 2-phenyl-3-(phenylselenonyl)-1-tosyl-1 H -indole in good yields.